2018
DOI: 10.1021/acschemneuro.8b00021
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Approach to Understanding the Organization of the Olfactory System in the Cuttlefish, Sepia officinalis

Abstract: Cephalopods are nontraditional but captivating models of invertebrate neurobiology, particularly in evolutionary comparisons. Cephalopod olfactory systems have striking similarities and fundamental differences with vertebrates, arthropods, and gastropods, raising questions about the ancestral origins of those systems. We describe here the organization and development of the olfactory system of the common cuttlefish, Sepia officinalis, using immunohistochemistry and in situ hybridization. FMRFamide and/or relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 90 publications
2
24
0
Order By: Relevance
“…HA‐LIR has been observed previously in the olfactory lobes (Scaros et al, ) but reported difficulties in the penetration of the requisite fixatives prevented the extensive exploration of HA distribution using immunochemistry only. Therefore, we report our findings using HDC ISH and anti‐HA IHC when available.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…HA‐LIR has been observed previously in the olfactory lobes (Scaros et al, ) but reported difficulties in the penetration of the requisite fixatives prevented the extensive exploration of HA distribution using immunochemistry only. Therefore, we report our findings using HDC ISH and anti‐HA IHC when available.…”
Section: Resultsmentioning
confidence: 89%
“…Scaros et al () previously showed evidence of HA‐LIR in cells of the olfactory lobes. Using HDC ISH, we identified the presence of HDC‐expressing cells as well.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations